Interreligious Dialogue in Context: Towards a Systematic Comparison of IRD-Activities in Europe - Lehmann, Karsten (Interdisciplinary journal for religion and transformation in contemporary society, 2020)
Abstract The article sketches the overall layout of the thematic issue of the ‘Journal of Religion and Transformation in Contemporary Societies ( JRAT )’ on Interreligious Dialogue ( IRD ) in context. It argues that an analysis of Interreligious Dialogue-activities in their socio-cultural contexts helps to counterbalance the long-standing individualistic bias of IRD -research. First, it presents a systematic description of the present state of the art that distinguishes two strands of IRD -research. Second, it argues for a European comparison, based upon the most recent findings from the ‘ SMRE – Swiss Metadatabase of Religious Affiliation in Europe’. The article closes with references to the structure of the present volume of JRaT to facilitate such a comparison.